ANALISIS YURIDIS PENGELOLAAN DANA PENSIUN LEMBAGA KEUANGAN OLEH PT BANK RAKYAT INDONESIA (Studi Putusan Nomor 65/PHI.G/014/PN.JKT.PST) - Endah Puspitasari (Jurnal Hukum dan Bisnis (Selisik), 2018)
Pension fund is the fund that intentionally collected to give benefits for the retired, passedaway or handicapped workers. This research’s objective is to understand themanagement of pension fund mechanism and also the employer’s accountability to theretired employee. This research uses normative legal research methods through literaturestudy, with the Court Verdict No. 65/PHI.G/014/PN.JKT.PST as the main data source